The Efficiency of Water in Supporting Local Wisdom and Food Sustainability in Subak Sange, Bali Indonesia - Ni Made Delly Resiani; I Wayan Sunanjaya (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2020)
Subak is local wisdom in Bali that has been practiced for centuries in managing irrigation water. Here we present the uniqueness of Subak to manage water with an example of Subak Sange, Gianyar, Bali. The field activity was carried out from April-September 2019. The research objectives were to analyze: (i) the characteristics of local wisdom in Subak Sange, (ii) the effect of irrigation water frequency on pest and disease outbreaks on tobacco yield, and (iii) the efficiency of water use in chili-tobacco intercropping. We combined several approaches to achieve the objectives, including an interview with farmer, diversity analysis, Romijn method, and revenue cost ratio. The results showed that the harmony of relations between farmers was bound by a belief in three elements socio-agrarian-religious. The excessive irrigation gave more pest and disease outbreaks, as shown in 6-irrigation frequencies. In addition, the occurrence of rotten root outbreaks was the highest (29%). The optimal frequency irrigation for yield of tobacco was 4-times, which produced 11.5 tons of dry chopped tobacco per hectare, and this frequency irrigation was much more efficient water use by 79% than rice plants. Based on revenue cost ratio analysis, the chili-tobacco intercropping with four times irrigation was feasible. The findings indicate that management of irrigation water in Subak Sange is promising to support food sustainability in the region.